Influence of Clay Content on Crack Evolution of Clay–Sand Mixture - Jiang, Xiangang; Huang, Qin; Zhang, Zongliang; Vallejo, Luis E.; Chen, Xiaoqing; Zhao, Wanyu; Deng, Hongyan; Liu, Xingrong; Song, Danqing; Chen, Zhuo (Frontiers in Earth Science, 2022)
Clay minerals have an important influence on the cracking of clay-sand mixture, but the quantitatively relationships between clay content and crack evolution of clay-sand mixture are still not clear. In order to explore the crack evolution process of clay-sand mixture under different clay contents conditions, we prepared nine groups of saturated clay-sand mixture samples with different clay contents, and carried out drying experiments and Brazilian tests. The geometric dimensions and development forms of soil cracking were quantitatively analyzed by taking pictures of the sample cracks, image processing and weighing the variation of the soil mass at the corresponding time during drying process. The results show that when the clay content was greater than 50%, the development process of the clay-sand mixture cracks can be divided into three stages——the formation stage of main cracks, the generation stage of the autonomously derived secondary fractures, and the stable stage of the crack width. When it was less than 50%, the cracks in the development process of clay-sand mixture cracks had the characteristics of short length, dense crack spacing, no main cracks, and no obvious stage. The clay could add the tensile strength of the mixture and restrain crack development. The clay content had a significant effect on the shrinkage cracking and crack development process of soil, which shows that with the increase of clay content, the tensile strength increases and restrain the crack development; the crack rate increases continuously and the width of cracks become larger; the lower the clay content, the lower the crack rate and the smaller the average crack width. The water content of samples with different clay soil contents all nonlinearly decrease with the increase of drying time, and the corresponding residual water content increases with the increase of clay soil content at the same time. The water content of initial cracking, stable crack length, stable crack width and stable block of clay-sand mixture increases with the increase of clay content, and the water content of stable crack length was the same as that of stable block number.